Pemikiran Metafisika Syah Waliyullah - Nur Shadiq Sandimula (Universitas Darussalam Gontor, 2022)
Metaphysics is a very important study in a knowledge discourse since it becomes the basic philosophy of a worldview of science. Among the Muslims who investigate the study of metaphysics is Shah Waliyullah al-Dihlawi. Al-Dihlawi had his metaphysical thoughts which are concerned regarding how Muslims should perceive the world around them. To discover his metaphysical beliefs, we should investigate his works that examine the topics of metaphysics. This research initiates by mentioning a brief description of al-Dihlawi intellectual biography and social background in his times to comprehend how his metaphysical thoughts were developed. A qualitative study was employed in this research by using descriptive analysis based on the historical-philosophical approach. Afterward, the scope of study of metaphysics was defined by classifying it into a study of ontology, theology, cosmology, and psychology to identify its concepts within al-Dihlawi works. This research shows that al-Dihlawi in the study of ontology had made clear that 'existence' is the reality itself (wujud munbasith) which is universal that was brought into existence by the Transcendent of Existence which is God. On theology, al-Dihlawi followed the Ahl al-Sunnah wa al-Jama'ah madhhab by affirming attributes of God and negating any similarities between God and the creations. On Cosmology, al-Dihlawi explained the beginning of creation and the connection between the spiritual and material world. And finally, on psychology, al-Dihlawi believed that the soul is the pure inner essence of a man which is originated from the Higher Realm that being placed into the material corpus and by that, it has a duality of inclination.